Assessing the Awareness and Attitude Towards COVID-19 Vaccination and Aids Factors among Jordanian People: A cross-sectional Study - Maqableh, Hindya; Makahleh, Nisrein; Ajlouny, Sara; Rislan, Maysaa; Alryhi, Taima’a; Fakhouri, Hussam N. (Jordan Journal of Pharmaceutical Sciences, 2024)
This study aimed to evaluate the awareness and attitudes toward COVID-19 vaccination among the Jordanian population. A cross-sectional survey was conducted using a validated questionnaire. The awareness and attitudes toward the COVID-19 vaccine were assessed via five-item and seven-item scales, respectively. The survey results were analyzed using SPSS with a chi-square test and multivariable logistic regression. A total of 407 participants were enrolled, with the majority being female (74.9%), under 49 years old (73.2%), holding a bachelor's degree (57.7%), and working in the private sector (46.2%). Results revealed a fairly high level of awareness about the COVID-19 vaccine (51.4%), with no significant association between awareness and demographic characteristics. While 51.4% of the participants perceived the importance of getting the vaccine, only 37.1% agreed that the newly developed vaccine was safe, and 77.4% expressed a preference for natural immunity. The overall attitude towards COVID-19 vaccination appears cautiously optimistic, with 60.2% of respondents scoring above Bloom's 60.0% cutoff point, despite mixed opinions on vaccine safety and necessity. Moreover, attitudes towards the vaccine showed a significant association with participants' age and occupation. Among the age group of 18-29 years old, 47.6% had a positive attitude towards the vaccine, compared to 33.3% in the 30-49 years old group, and 38.5% in the ≥50 years old group. In terms of occupation, 30.7% in the public sector had a positive attitude, compared to 44.1% in the private sector and 48.5% among students. Given the mixed but cautiously optimistic attitudes towards COVID-19 vaccination observed among the Jordanian population, this study underscores the critical importance of targeted educational and communication strategies. Such initiatives should focus on enhancing the perception of vaccine safety and efficacy to improve vaccination acceptance and uptake across different age and occupational groups within Jordan.